Rethinking heart failure clinical trials: the heart failure collaboratory - Alkalbani, Mutaz; Psotka, Mitchell A. (Frontiers in Cardiovascular Medicine, 2024)
The Heart Failure Collaboratory (HFC) is a consortium of stakeholders in the heart failure (HF) community that aims to improve the infrastructure of clinical research to promote development of novel therapies for patients. Since its launch in 2018, HFC has implemented several solutions to tackle obstacles in HF clinical research including training programs to increase the number of clinicians skilled in conducting clinical trials, novel study designs, and advocacy for a diverse and inclusive HF research ecosystem. We highlight some of the HFC successes since its establishment.